2019
DOI: 10.22146/jkap.37913
|View full text |Cite
|
Sign up to set email alerts
|

Does Public Service Motivation Matter to Employees’ Performance and Organizational Commitment in Sub-district Offices?

Abstract: Many studies on Public Service Motivation (PSM) were conducted extensively in the developed countries, including US and Western Europe. In addition, some research on PSM has been conducted in Eastern Asia, all which affirm the positive role that plays in in shaping the public sector. That said, studies on PSM in developing countries, including Indonesia is still limited. This is despite the fact that previous research associate PSM with improving public sector performance. The objective of this study is to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Public service motivation is defined as prosocial and altruistic when the subject experiencing it serves the public or society [8] Previous research found that employees who work for the public perform better when their work has a positive impact on the larger community [9]. Individuals who experience public service motivation have a motivating force or drive that drives them to engage in action positively for the public while also helping in shaping the welfare of society [10].…”
Section: Public Service Motivationmentioning
confidence: 99%
“…Public service motivation is defined as prosocial and altruistic when the subject experiencing it serves the public or society [8] Previous research found that employees who work for the public perform better when their work has a positive impact on the larger community [9]. Individuals who experience public service motivation have a motivating force or drive that drives them to engage in action positively for the public while also helping in shaping the welfare of society [10].…”
Section: Public Service Motivationmentioning
confidence: 99%